Appraisal of clinical practice guidelines for the evaluation and management of neck masses in children. (20th April 2021) - Shin, Max; Prasad, Aman; Arguelles, Gabriel R; Wakim, Jonathan J; Chorath, Kevin; Moreira, Alvaro; Rajasekaran, Karthik
Abstract : Aim: The purpose of this systematic review was to use the Appraisal of Guidelines for Research and Evaluation tool to assess the methodological quality of clinical practice guidelines (CPGs) for the workup and management of paediatric neck masses. Methods: MEDLINE, Embase, Cochrane and grey literature were searched to identify CPG incorporating paediatric neck masses. Four authors with previous training of the Appraisal of Guidelines for Research and Evaluation tool evaluated the included studies. Results: Nine studies met inclusion criteria. The highest scoring domains were 'Scope and Purpose' (74.0 ± 4.5) and 'Clarity of Presentation' (72.9 ± 6.3). The lowest scoring domains were 'Rigour and Development' (18.8 ± 7.5) and 'Applicability' (23.7 ± 6.1). One study was 'High' quality, three received scores of 'Average' and five were found to be 'Low' quality. Conclusion: The majority of paediatric neck mass CPGs were low to average quality. The domains in need of greatest improvement were 'Rigour and Development' and 'Applicability', suggesting significant concerns in current CPGs focused on paediatric neck masses.